A re-configurable MASH 2-2 bandpass DQEFM for multi-standard applications. Issue 10 (3rd October 2019) - Sebastian, Rijo; A. V, Jos Prakash; Jose, Babita R.; TK, Shahana; Mathew, Jimson
ABSTRACT: The design, analysis and implementation of a multi-stage noise shaping (MASH) bandpass modulator that employs a differentially quantized error feedback modulator (DQEFM) structure is described. The re-configurability, reduction of power-hungry active blocks and reduced sensitivity to circuit non-idealities makes this proposed bandpass modulator a suitable candidate for a digital intermediate frequency receiver system. The mathematical analysis and simulation results indicate the resemblance of the proposed modulator with the conventional sigma-delta modulator. The circuit level simulations indicate the better performance of the proposed modulator in terms of hardware complexity and power. The proposed cascaded modulator when implemented using 45nm CMOS process attains a signal-to-noise plus distortion ratio of 81.4 dB for a bandwidth of 200 kHz (GSM) and 61 dB for a bandwidth of 5 MHz (WCDMA). The circuit level simulation of the proposed bandpass architecture indicates a power consumption of 3.7 mW and 6.9 mW for GSM and WCDMA modes with 1V supply.